Study on Ball Clay-Based Eco-Friendly Deicing Agents for Road Dust Suppression - Min-Zy Kim; Su-Yong Lee; Chi-Ho Kim; Gyu-Jung Jung (대한환경공학회지, 2025)
The increasing use of deicing agents during winter, driven by abnormal climate changes such as global warming, has raised environmental concerns, including soil salinization, plant growth inhibition, road infrastructure corrosion, and elevated particulate matter (PM10) levels near roads. This study aimed to develop an eco-friendly deicing agent incorporating Ball Clay (Eco-Friendly Deicing Agent with Ball Clay, EDBC) and evaluate its dust suppression performance and physicochemical properties compared to conventional chloride-based deicing agents. The dust suppression performance of EDBC was evaluated using PM10 concentration measurements in a controlled chamber, comparing its effectiveness at different concentrations (5% and 30%) with calcium chloride (CaCl2) and sodium chloride (NaCl). Additionally, Scanning Electron Microscopy and Energy Dispersive Spectroscopy (SEM/EDS) analyses were conducted to assess the surface structure and physicochemical interactions of EDBC with dust particles. At a 5% concentration, EDBC achieved an average PM10 concentration of 174.03 μg/m3, significantly lower than CaCl2 (405.83 μg/m3) and NaCl (1256.67 μg/m3). Even at a 30% concentration, EDBC maintained the lowest dust concentration of 101.8 μg/m3. SEM/EDS analysis confirmed that EDBC formed a dense and uniform surface structure, enabling strong physicochemical binding to dust particles. In contrast, CaCl2 and NaCl, due to their high solubility and hygroscopic nature, showed limited dust suppression efficiency and posed challenges for long-term environmental sustainability. These results suggest that EDBC is a promising alternative to traditional chloride-based deicing agents, providing both effective dust control and environmental benefits.